2003
DOI: 10.1038/sj.bjc.6600758
|View full text |Cite
|
Sign up to set email alerts
|

Particulate debris from a titanium metal prosthesis induces genomic instability in primary human fibroblast cells

Abstract: Previous studies detected both lethal and cumulative chromosomal aberrations in bone marrow and peripheral blood of patients with worn hip and knee replacements. This study shows that wear debris from a worn titanium metal on high-density polyethylene hip replacement also produces chromosomal instability and reproductive failure in cell culture. The progeny of these treated cells also displayed chromosomal instability, mainly consisting of chromatid breaks and minutes, and reproductive failure as determined by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(56 citation statements)
references
References 43 publications
2
52
0
2
Order By: Relevance
“…Macrophage activation caused by titanium particles and increased cell mediator release has been observed in vitro and in vivo [18,19]. In vitro chromosomal damage caused by high concentrations of titanium particles have also been reported [5,6]. Nevertheless, such reactions depend strongly on the applied particle or ion concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Macrophage activation caused by titanium particles and increased cell mediator release has been observed in vitro and in vivo [18,19]. In vitro chromosomal damage caused by high concentrations of titanium particles have also been reported [5,6]. Nevertheless, such reactions depend strongly on the applied particle or ion concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Coen et al (2001Coen et al ( , 2003 have shown that the metal ions, cadmium and nickel, as well as orthopaedic wear debris from a titanium aluminium vanadium alloy hip replacement cause genomic instability. This phenomenon, usually characteristic of radiation exposure (Seymour et al, 1986;Kadhim et al, 1992), resulted in a persistent reduction in clonogenic survival and increase in chromosome aberrations in the distant progeny of cells which appeared to have completely recovered from the exposure.…”
Section: Introductionmentioning
confidence: 99%
“…The present study results showed that women with the highest tertile of urinary titanium had 47% increased risk of breast cancer, when compared with those with the lowest tertile, although it was not statistically significant. In addition, a previous experimental study has also demonstrated that wear debris from a worn titanium metal produces chromosomal instability (chromatid breaks and minutes), similar to those caused by heavy metals of cadmium and nickel (35).…”
Section: Discussionmentioning
confidence: 93%